La mortalité gendarmique sous l’Occupation (1940-1944). Les corps d’un Corps - Emmanuel Chevet (Amnis)
At the Liberation, the French “Gendarmerie”, facing the result of a four-year professional submission to the occupying forces, has to legitimate itself. This past full of professional and morals contradictions, only exhibits a partisan picture of the institution. This smoothed representation appears in the study of the victims of this Corp. The memory of gendarmes killed in the “Maquis” overshadows the remembrance of a multiple and complex mortality. Some of its ambivalent aspects are forgotten if not neglected.